Analysis of citizen service strategies established in the Ministry of National Education, period 2019 (2019)
This document analyzes how the Ministry of Education as a state entity, must be focused on customer satisfaction, the culture of good service is an essential element in the realization of an efficient service program that responds to the needs and expectations of the citizen. For this, the Ministry generates strategies in order to make a change in the culture of the service and thus establish an approach in such a way as to ensure compliance with the important and essential elements of the strategic direction and plan of the entity, talent human and citizen care standards set. In the Ministry, the implementation of strategies is carried out in order to solve the needs and requirements of the citizens, identify the shortcomings and good practices of citizen service and, based on this information, changes are generated to improve the service culture and transform the organization with the implementation of programs that involve moments of truth in citizen service.